As masculinidades na escola: histórias e memórias da escolarização de alunos da Educação de Jovens e Adultos da rede municipal de João Pessoa. - Menezes., Cristiane Souza de (2008)
The following research analyses how masculinity concepts of the EJA (Education for Young Adults) students have interfered with their schooling processes. This analysis uses the theoretical-methodological basis of Gender Studies and New Cultural History. The most used methodology in this research is oral history. For that end, we ran several semi-structured interviews in which we collected the tales and memories of EJA students, especially the ones about their schooling process and their socialization. The subjects of the research were ten male students from two municipal schools from João Pessoa, Paraíba. Careful observation and documental analysis were also used as complementary techniques. The results point out that the student's concepts of masculinity are based in the assumption that different genders have different 'natures'. These natures would determine different appropriate behaviors and would help set the limits between male and female in the school grounds. A simple example is the widely accept notion that boys are more inclined to mess around while girls tend to be more dedicated. This aspect is actually mentioned as a factor in schooling failure (evasion, reprobation, etc). On the other hand, the notion that 'boys are messy' was associated with boys and young adults, while for the subjects of the research to 'man up' is to show responsibility, respect and honesty. Some studies also point this out, showing that masculinity is associated with different meanings at different ages; the way the educational process is seen changes as the male takes on the responsibilities of adult life. These ideas are deeply connected with the importance given to entering the work life (which at that point the male reaches the much valued role of provider). The interviews also indicate that social and economical conditions and the lack of schools on some of Paraíba's towns are major factors in the schooling process of the research subjects.